Budget Mechanism of Regional Innovation Policy in Russia: Supply Chain Planning, Scheduling and Control - Elena V. Krasova (International Journal of Supply Chain Management, 2019)
Supply chain management (SCM) has been stressed as a remedy to many of the underlying issues in the construction industry. The article is devoted to an actual topic in Russia related to the development and improvement of the budget mechanism for regional innovation policy. The article’s main scientific and practical problem is the inefficiency of the current innovation policy budget mechanism, based on centralized resource support of the territory innovative development and the weak role of the regions in the country innovation infrastructure formation. The main hypothesis of the research is that the budget mechanism improvement is a necessary and priority factor for resource provision efficiency increase concerning innovation activity in Russia, and also represents an integral part of territorial management optimization concerning innovation development in Russia. The purpose of the research is to actualize the current situation and the problems associated with the implementation of the regional innovation policy budget mechanism in Russia. Based on the researches about existing innovation development model in the country, the author identifies the most important problems in the budget mechanism functioning of regional innovation policy at the present stage: the low role of the regions in the resource provision for innovation activity and the weak, ineffective modern instruments of the regional budget mechanism. The article reflects the low degree of region involvement in the innovation financing process, considers the phenomenon of multidirectional management decisions due to the inconsistency of the various elements in the program-target planning for innovative development.